HUBUNGAN KADAR ANTIBODI RESEPTOR ASETILKOLIN DENGAN DERAJAT KEPARAHAN PENYAKIT MIASTENIA GRAVIS DI RS CIPTO MANGUNKUSUMO - Manfaluthy Hakim; Fika Tiara; Ahmad Yanuar; Winnugroho Wiratman; Luh Ari Indriawati; Astri Budikayanti; Fitri Octaviana (NEURONA, 2020)
Introduction: Acetylcholine receptor (AChR) antibody is main antibody in pathogenesis of myasthenia gravis (MG). AChR antibody is an important diagnostic tests. Myasthenia gravis clinical features can be divided into ocular, generalized and bulbar MG. Severity of MG can be assessed based on MG composite score (MG-cs). Aim: To evaluate association between level of AChR antibody and MG severity based on MG severity in Cipto Mangunkusumo Hospital. Methods: This was a descriptive-analytic cross-sectional study which were done at Cipto Mangunkusumo Hospital during January to November 2017. Inclusion criteria were MG patients aged 18-75 years old. Assessment of MG composite score and blood withdrawal were performed at the same time. The level of AChR antibody was measured by ELISA method. Results: There were 72 subjects met inclusion criteria. Mean age was 43 years old (SD 12.56) with proportion higher in women (2.5:1). Ocular MG was the most initial symptom (79.2%) and early onset was the most common(77.8%). There were 59.7% subject who had seropositive AChR antibody. There was no significant association between seropositive AChR antibody and gender, age of onset, MG type, MGFa classification, immunotherapy. There was no association between level of AChR antibody and MG-cs(p=0.727). Discussion: There wasn’t any association between level of AChR antibody and MG severity based on MG-cs. Keywords: AChR antibody, MG composite score, MG severity